Proterozoic accretionary tectonics in the east Kimberley region, Australia - Lindsay, M.; Occhipinti, S.; Aitken, A.; Metelka, V.; Hollis, Julie; Tyler, I. (Elsevier BV, 2016)
The east Kimberley region contains well-preserved tectonic structure dating back to the Earth's most significant stage of continental growth: the assembly of the Nuna supercontinent. An integrated geological-geophysical investigation of this region has been conducted and reveals insight into its tectonic evolution, including potential influence of significant crustal-scale structures in the development of regional architecture, the emplacement of magma, and the relationship of these structures to large-scale deformation. Some newly interpreted features include a north-trending structure, and three north-west trending structures that segment the north-east trending orogen. The central segment of the orogen is a zone of higher metamorphic grade, and is host to a distinct gravity high. This gravity high can be explained by excess mass in the mid-crust. This anomaly is consistent with either a large mafic-ultramafic intrusion or a high-density crustal fragment. Possible tectonic models to explain the geophysical and metamorphic anomalies involve, in the latter case, the accretion of a crustal fragment to the Kimberley Craton prior to the 1865-1850 Ma H ooper Orogeny or, in the former case, intrusion of voluminous mafic magmas into the middle crust. Whether by igneous or structural means, we consider the development of this anomalous region to be a result of along-strike variations in subduction dynamics. These were perhaps driven by variations in slab-geometry accommodated by the orogen-normal structures we identify. The orogen-normal structures are interpreted to be crustal-scale faults, along which significant vertical displacement occurred when a crustal fragment collided with Kimberley Craton and exhumed high-grade metamorphic rocks to the surface.